Pengetahuan Konsumen dan Keputusan Menjadi Nasabah Lembaga Keuangan Mikro Syariah - Intan Qurratulaini (Jihbiz : Jurnal Ekonomi, Keuangan dan Perbankan Syariah, 2020)
This study aims to determine the effect of consumer knowledge about Islamic banking on the decision to become a customer at a Sharia Microfinance Institution (LKMS). A research method is a quantitative approach, where data is obtained through questionnaires (questionnaires), interviews, and documentation. After the data was obtained, the researcher analyzed it using regression analysis. Partial calculation results show that consumer knowledge about Islamic banking influences the decision to become a customer. One of the toughest challenges that many LKMS are now facing is the many accusations that LKMS is just conventional financial institutions with a sharia label added. LKMS consumers, becoming customers only want to secure their money or because of the profit-sharing offered by LKMS so that they can facilitate their economic path, besides that, they are also interested in the Islamic label or sharia system developed by the LKMS but in detail, they do not understand the process of implementing the sharia, but whether One's knowledge of sharia in the LKMS is a factor in the decision to become an interesting customer for further investigation.